Perinatal development of central vestibular neurons in mice - Dubois, Christophe J.; Cardoit, Laura; Simmers, John; Lambert, François M.; Thoby-Brisson, Muriel (Frontiers in Neuroscience, 2022)
Central circuitry of the vestibular nuclei integrates sensory inputs in the adaptive control of motor behaviors such as posture, locomotion and gaze stabilization. Thus far, such circuits have been mostly examined at mature stages, whereas their emergence and early development have remained poorly described. Here, we focused on the perinatal period of murine development, from embryonic day E14.5 to postnatal day P5, to investigate the ontogeny of two functionally distinct vestibular neuronal groups, neurons projecting to the spinal cord via the lateral vestibulo-spinal tract (LVST) and commissural neurons of the medial vestibular nucleus that cross the midline to the contralateral nucleus. Using transgenic mice and retrograde labelling, we found that network-constitutive GABAergic and glycinergic neurons are already established in the two vestibular groups at embryonic stages. Although incapable of repetitive firing at E14.5, neurons of both groups can generate spike trains from E15.5 onwards and diverge into previously established A or B subtypes according to the absence (A) or presence (B) of a two-stage spike after-hyperpolarization. Investigation of several voltage-dependent membrane properties indicated that solely LVST neurons undergo significant maturational changes in their electrophysiological characteristics during perinatal development. The proportions of A vs B subtypes also evolve in both groups, with type A neurons remaining predominant at all stages, and type B commissural neurons appearing only postnatally. Together, our results indicate that vestibular neurons acquire their distinct morpho-functional identities after E14.5 and that the early maturation of membrane properties does not emerge uniformly in the different functional subpopulations of vestibulo-motor pathways.